Family-Centered Care in Aphasia: Assessment of Third-Party Disability in Family Members With the Family Aphasia Measure of Life Impact. Issue 1 (January 2019) - Grawburg, Meghann; Howe, Tami; Worrall, Linda; Scarinci, Nerina
Abstract : More than 50 years of research has demonstrated the profound effect that aphasia has on people with the condition and their family members. In the International Classification of Functioning, Disability and Health, the World Health Organization described the impact of an individual's health condition on a significant other as "third-party disability." Recent research has described how third-party disability can occur in family members of people with aphasia post-stroke. Despite the extensive history and ongoing relevance of these findings, family-centered rehabilitation has been slow to integrate into clinical practice and policy. The aims of this article are (1) to provide an overview of third-party disability in family members of people with aphasia; (2) to consider how third-party disability can be addressed through family-centered care and to identify some of the barriers to family-centered care; and (3) to describe The Family Aphasia Measure of Life Impact (FAMLI), a tool for measuring third-party functioning and disability in family members of people with aphasia, identifying family rehabilitation needs, and measuring outcomes of family-centered care.